Corporation Nation - Wright, Robert E. (Robert Eric), 1969- (Book collections on Project MUSE., 2014)
Drawing on legal and economic history, Robert E. Wright traces the development of corporate institutions in America, connecting today's financial failures to weakened internal corporate regulation.